2009
DOI: 10.1016/j.nut.2008.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Refractory myasthenia gravis, dysphagia and malnutrition: A case report to suggest disease-specific nutritional issues

Abstract: Objective: We describe a case of refractory myasthenia gravis with bulbar involvement and the nutritional treatment solutions proposed to treat the associated dysphagia and malnutrition. Methods: A 39-y-old woman with refractory myasthenia gravis was referred to our clinical nutrition unit for deteriorating dysphagia and progressive malnutrition.Results: The first-line nutritional approach consisted of dietary counseling and thickened meals. Unfortunately, no adequate oral intake was achieved and an enteral nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In regard to this, we believe that ethical issues also should be taken into account and clearly stated. This is what has been suggested by the European Society for Parenteral and Enteral Nutrition (ESPEN) 2 and what we have learned from our own experience, 3 particularly when the selection of enteral access device must be made. "Prior to the insertion of an enteral feeding tube, each case should be considered on its own merits, taking into account the clinical situation, diagnosis, prognosis, ethical issues, the expected effect on the patient's quality of life and the patient's own wishes."…”
Section: Dear Editorsupporting
confidence: 59%
See 1 more Smart Citation
“…In regard to this, we believe that ethical issues also should be taken into account and clearly stated. This is what has been suggested by the European Society for Parenteral and Enteral Nutrition (ESPEN) 2 and what we have learned from our own experience, 3 particularly when the selection of enteral access device must be made. "Prior to the insertion of an enteral feeding tube, each case should be considered on its own merits, taking into account the clinical situation, diagnosis, prognosis, ethical issues, the expected effect on the patient's quality of life and the patient's own wishes."…”
Section: Dear Editorsupporting
confidence: 59%
“…2 In a discussion on this issue, we have recently reported the clinical case of a woman suffering from myasthenia gravis. 3 In this case, neurogenic dysphagia, frequently presenting "a poussés" (phases of remission alternating with symptoms exacerbation), inability to obtain adequate intakes, and malnutrition (weight loss >25% of initial body weight), which are established indications for gastrostomy, were effectively resolved by the patient herself through the intermittent self-placement of a nasogastric (NG) tube for overnight feeding during myasthenic exacerbations. This happened because the patient refused gastrostomy placement, and the maintenance of the NG tube during daylight hours was also unacceptable to the patient ("something like a trunk").…”
Section: Dear Editormentioning
confidence: 94%
“…The symptoms of refractory MG may have consequences beyond the initial medical aspects, as illustrated in case studies; for example, patients may experience malnutrition due to escalating dysphagia. 17 The prevalence of sleep-disordered breathing and obstructive sleep apnea is higher in patients with MG than in the general population, 18 and sleep disturbance in patients with MG has been shown to correlate with lack of remission and the need for immunosuppressive agents, suggesting a higher prevalence in patients with refractory MG. 19 Ongoing disease can also interfere with the ability to work because of functionally limiting fatigable weakness after short periods 20 or diplopia, 15,21 which can restrict the patient's independence and flexibility because of an inability to drive. A study of 917 patients in Japan showed a significant positive correlation between insufficient control of MG symptoms (a definition of refractory MG) and unemployment or unwilling job transfer.…”
Section: Introductionmentioning
confidence: 98%